Rethinking secularism - Calhoun, Craig J.; Juergensmeyer, Mark; VanAntwerpen, Jonathan (Oxford University Press, 2011)
This collection of essays presents groundbreaking work from an interdisciplinary group of leading theorists and scholars representing the fields of history, philosophy, political science, sociology, and anthropology. The volume will introduce readers to some of the most compelling new conceptual and theoretical understandings of secularism and the secular, while also examining socio-political trends involving the relationship between the religious and the secular from a variety of locations across the globe.